Between‐Batch Pharmacokinetic Variability Inflates Type I Error Rate in Conventional Bioequivalence Trials: A Randomized Advair Diskus Clinical Trial. Issue 3 (26th November 2016) - Burmeister Getz, E; Carroll, KJ; Mielke, J; Benet, LZ; Jones, B
Abstract : We previously demonstrated pharmacokinetic differences among manufacturing batches of a US Food and Drug Administration (FDA)‐approved dry powder inhalation product (Advair Diskus 100/50) large enough to establish between‐batch bio‐inequivalence. Here, we provide independent confirmation of pharmacokinetic bio‐inequivalence among Advair Diskus 100/50 batches, and quantify residual and between‐batch variance component magnitudes. These variance estimates are used to consider the type I error rate of the FDA's current two‐way crossover design recommendation. When between‐batch pharmacokinetic variability is substantial, the conventional two‐way crossover design cannot accomplish the objectives of FDA's statistical bioequivalence test (i.e., cannot accurately estimate the test/reference ratio and associated confidence interval). The two‐way crossover, which ignores between‐batch pharmacokinetic variability, yields an artificially narrow confidence interval on the product comparison. The unavoidable consequence is type I error rate inflation, to ∼25%, when between‐batch pharmacokinetic variability is nonzero. This risk of a false bioequivalence conclusion is substantially higher than asserted by regulators as acceptable consumer risk (5%).